Determining of Chemical Bond Properties in Hydrocarbons by Using Infrared Spectrum - Khair Oghli, Puhandoy Amir Mohammad (Journal for Research in Applied Sciences and Biotechnology, 2023)
The spectroscopy of infrared is type of vibrational spectroscopy which is bases on the fact that a molecule absorbs infrared radiation, it is chemical bond vibrate. The bonds can stretch, contract, and bend have characteristic vibrations depending on the atoms in the bond, the number of bonds, and the orientation of those bonds with respect to the rest of the molecule. The troughs in the spectrum are caused by the absorption of infrared frequencies by chemical bonds, which are often characteristic of combinations of atoms or functional groups. The light of infrared can create the bond angle between the atoms in a compound to decrease and increase as it reaches back to equilibrium. While a molecule of a compound absorbs the light of infrared radiation, its chemical bonds vibrate. When the radiation is absorbed, the bond can stretch, contract, and bend. This is the reason that the infrared spectroscopy is a type of vibrational spectroscopy. When the bond absorbs the radiation that matches the frequency of the vibration of one of its bonds and this means that the molecule is exposed to infrared radiation. The radiation of infrared absorbed allows the bond to vibrate a bit more, that is increase the amplitude observation, but the vibrational frequency will remain the same.